Simulating the Production of Surfactant α-MES (a Methyl Ester Sulfonate) from FAME (Fatty Acid Methyl Ester) Using the Superpro Designer Application - Verlanda, Fransiskus Fyrmansah; Chandra, Shofie; Ananta, Vania Talitha; Noviana , Siska; Ivanka , Tiara Tri Vira; Sitompul , Aprina Sasmitha; Fitri, Rahmatil (Journal of Innovation Process and Environmental Technology, 2025)
The demand for energy continues to grow, while the availability of fossil fuel-based energy is gradually decreasing. As the population increases, so does the need for oleochemical products. One commonly utilized product in the oleochemical industry is surfactants. These are molecules characterized by the presence of both hydrophilic (water-attracting) and lipophilic (oil-attracting) groups in a single structure. The production of surfactants from FAME (Fatty Acid Methyl Ester) begins with a sulfonation step, during which FAME reacts with a reagent like oleum SO3. However, to ensure the process is efficient and effective, optimization is necessary. A detailed simulation using SuperPro Designer software can help model the production process. The results of these simulations reveal that optimizing parameters such as temperature, pressure, and reactant ratios can significantly enhance the production efficiency of surfactants. Therefore, process optimization through simulation can be a key factor in improving both the efficiency and sustainability of the oleochemical industry.